A AN ANALYSIS OF IDIOMATIC EXPRESSION USED IN HACKSAW RIDGE MOVIE (2016) - Harliansyah, Rivaldo; Kasmaini; Fadhli, Muhammad (Wacana: Jurnal Penelitian Bahasa, Sastra dan Pengajaran, 2024)
This research aims to determine the types and meanings of Idiomatic expressions in the Hacksaw Ridge Movie. This research used a qualitative method. The object of this research is the script of dialogues and narrations of the characters in Hacksaw Ridge Movie., namely Whole script movie. The researcher used data sheets and tables as instruments. The researcher identified and categorized each expression based on Makkai's theory (2013) and using two dictionaries related to idioms, namely Merriam Dictionary of Idioms, Dictionary of American Idioms by McGraw-Hill's, , then matched the meanings of Idiomatic expressions from the dictionaries with the co-text contained in the dialogues or narrations of the characters to analyze the data. The results showed that there were six types of lexemic idiomatic expressions in the Hacksaw Ridge Movie., namely Sesemic idiom (Proverbial Idioms, Familiar quotation idioms, Idiomaticity in institutionalized understatement, Idiomaticity in institutionalized hyperbole) and Lexemic Idiom  (Phrasal Verb idioms, Tournure idioms, Irreversible Binomial idioms, Phrasal Compound idioms, Incorporating Verb idioms, and Pseudo idioms). In determining the meaning must be based on the co-text because an idiom contains many meanings.